Assessment Methodologies: energy, mobility and other real world application - Joana Dias (Investigação, 2015)
The use of assessment methodologies is becoming increasingly important in the decision making process under very different environments. There are increasing concerns about making the best possible use of the limited available resources. There is also an increasing will of justifying the decisions in a sound way. This is even more important when considering public spending, public scrutiny and governance accountability. The use of recognized assessment techniques is actually mandatory in many situations, considering environmental, social, economic and sustainability concerns. This book gathers contributions from several authors, advancing the state-of-the-art and presenting examples of applications of assessment methodologies in energy, mobility and other real world applications.